Jean-Marie Le Pen vs. Marine Le Pen : un ‘ethos émotif’ différent ? - Baider, Fabienne; Constantinou, Maria (Studia Romanica Posnaniensia, 2015)
This paper examines how the Front National’s electoral victories could be explained, partially, in terms of a new discursive rhetoric adopted by Marine Le Pen. In order to compare rhetorical strategies used by both Marine and Jean-Marie Le Pen and their impact on their followers, we use comparable data, which consist of press articles published during the presidential campaigns of each politician and postings by online discussants related to interviews. Using corpus linguistics tools and lexical semantics, we assess how differently both leaders position themselves emotionally and how this emotional positioning is reconstructed within the postings of the viewers. Although no important quantitative difference can be observed in the number of emotion key-words they used respectively, a shift in both politicians’ rhetoric positioning can be observed when analyzing the context in which these keywords are embedded. If Jean-Marie Le Pen focuses on negative feelings towards the Other (anger, resentment), Marine Le Pen promotes a positive ethos (empathy) in order to detoxify the image of her party and broaden her electoral base.